Clinical Success Stenting Distal Bronchi for "Lobar Salvage" in Bronchial Stenosis. Issue 1 (January 2018) - Sethi, Sonali; Gildea, Thomas R.; Almeida, Francisco A.; Cicenia, Joseph C.; Machuzak, Michael S.
Abstract : Background: Airway stents are traditionally used in central airway obstructions to maintain airway patency. Historically, distal bronchial stenting within lobar and segmental bronchi has not been amenable to stenting. In addition, there are questionable benefits to stenting small airways. The Atrium iCast stent is a polytetrafluoroethylene covered stainless steel balloon deployed stent which can be deployed through a flexible bronchoscope under direct visualization. The purpose of this study was to assess the feasibility, complications, and long-term impact of using this stent in patients with lobar bronchial stenosis either secondary to malignancy or benign etiologies. Methods: All records of patients who had the placement of an iCast stent were reviewed over 3.5 years. For each patient the age, sex, location, histology, stent size, duration of stent placement, radiographic improvement, and complications were collected. Results: A total of 122 iCast stents were deployed in 38 patients with lobar bronchial stenosis. The average age was 58 years with 50% male. The etiology included 45% malignant and 55% due to benign conditions. In total, 18.5% patients had stents placed in >1 segment. There was an average of 4 procedures per patient with a mean time to stent revision or removal of 85 days. All patients had symptomatic or radiographic improvement. Common complications included migration (10%), granulation tissue formation (5%), deployment malfunction (2%), stent dislodgement immediately after deployment (2%), mucous plugging (1%), and tumor occlusion (1%). Conclusion: Stenting small airways with lobar salvage is feasible and improves symptoms and radiographic outcomes.